Challenges in the culture-independent analysis of oral and respiratory samples from intubated patients - Lazarevic, Vladimir; Gaïa, Nadia; Emonet, Stéphane; Girard, Myriam; Renzi, Gesuele; Despres, Lena; Wozniak, Hannah; Yugueros Marcos, Javier; Veyrieras, Jean-Baptiste; Chatellier, Sonia; van Belkum, Alex; Pugin, Jérôme; et al. (Frontiers in Cellular and Infection Microbiology, 2014)
The spread of microorganisms in hospitals is an important public health threat, and yet few studies have assessed how human microbial communities (microbiota) evolve in the hospital setting. Studies conducted so far have mainly focused on a limited number of bacterial species, mostly pathogenic ones and primarily during outbreaks. We explored the bacterial community diversity of the microbiota from oral and respiratory samples of intubated patients hospitalized in the intensive care unit and we discuss the technical challenges that may arise while using culture-independent approaches to study these types of samples.